Validity of Absentee Land Ownership Based on Sale and Purchase Deed Number 01/DEPOK/1967 (Case Study of Supreme Court Decision Number 599/K/PDT/2019) - Saputri, Widya Anugrah; Handayani, Sri Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the implementation of the land reform program, deviations occurred by tenant farmers as recipients of land redistribution by transferring ownership rights of absentee land to others through a deed of sale and purchase, without the approval of the Minister of Agrarian Affairs. This happened because the tenant farmers did not fulfill their obligation to pay the required fees after being granted the agricultural land, leading to land disputes, as seen in the District Court Decision No. 165/Pdt.G/2014/PN in conjunction with the Bandung High Court Decision No. 346/PDT/2016/PT.BDG in conjunction with the Supreme Court Decision No. 599 K/Pdt/2019. The issue at hand is the validity of the transfer of ownership rights of absentee land based on the deed of sale and purchase No. 01/Depok/1967 in this case and the impact of the Supreme Court Decision No. 599/K/PDT/2019 on the validity of absentee land. This thesis employs normative juridical research methods. The validity of the deed contradicts Article 14 paragraph (4) of Government Regulation No. 224 of 1961 concerning the Implementation of Land Distribution and Compensation, and its impact is that the land returns to the original owner before the land was declared absentee, with the land being returned to the respective heirs. However, the heirs do not reside where the land is located, thus they must immediately transfer the agricultural land to another party who resides in the same area as the land, in accordance with Article 3c of Government Regulation No. 41 of 1964 concerning the Implementation of Land Distribution and Compensation.